Geographic context scanning & analysis: il Modello Di Riferimento e le Operazioni - Rosina, Maurizio (GEOmedia, 2013)
The aim of the article is to define a Reference Model and the operators which allow to perform the activities of Geographic Context Scanning & Analysis. The theory and methods exposed will contribute to the evolution of the framework GEOPOI 2.0, developed and delivered by Sogei and acc essed as a SaaS (Software as a Serv ice) by a number of Public Administrations for your own institutional tasks.